Robot-Assisted Laparoscopic Partial Colpectomy and Intracorporeal Ileal Conduit Urinary Diversion (Bricker) for Cervical Adenocarcinoma Recurrence - Jennifer Uzan; Caroline Cornou; Chérazade Bensaid; François Audenet; Charlotte Ngô; Anne-Sophie Bats; Fabrice Lecuru (Hindawi Limited, 2015)
Ileal conduit urinary diversion (Bricker) is a standard surgical open procedure. The Da Vinci robot allowed precision for this surgical procedure, especially for intracorporeal suturing. Meanwhile, few reports of robot-assisted laparoscopic ileal conduit diversion (Bricker) are described in the literature. We report the case of a 69-year-old patient with a vaginal recurrence of cervical adenocarcinoma associated with vesicovaginal fistula treated by robot-assisted laparoscopic partial colpectomy and ileal conduit urinary diversion (Bricker). The robot-assisted laparoscopic procedure followed all surgical steps of the open procedure. Postoperative period was free of complications.